Allelopathic effects of diatom filtrates on the toxic benthic dinoflagellate Ostreopsis cf. ovata. (October 2017) - Pichierri, Salvatore; Accoroni, Stefano; Pezzolesi, Laura; Guerrini, Franca; Romagnoli, Tiziana; Pistocchi, Rossella; Totti, Cecilia
Abstract: Ostreopsis blooms regularly occur in many Mediterranean coastal areas in late summer-autumn. In the northern Adriatic Sea, Ostreopsis blooms affect diatom-dominated microphytobenthic communities. In this study, the effects of the filtrates of some diatom species, both benthic ( Tabularia affinis, Proschkinia complanatoides and Navicula sp.) and planktonic ( Thalassiosira sp. and Skeletonema marinoi ) on cell morphology, cytological features and growth of O . cf. ovata were investigated. Our results showed a marked decrease of O . cf. ovata growth when cells were exposed to all diatom filtrates tested. The highest inhibitions were observed for exposures to P. complanatoides and Navicula sp. filtrates (92.5% and 80%, respectively) and increased with the age of diatom culture. Moreover, a clear DNA degradation and abnormal forms of O. cf. ovata cells (83.8% of the total) were found at the highest concentrations using Navicula sp. filtrate after 10 days of the inoculum. Highlights: Inhibitory effect of planktonic and benthic diatoms on Ostreopsis growth was shown. Inhibitory effect increased with the age of diatom cultures. All the investigated diatom species exerted negative effects toward Ostreopsis . Proschkinia and Navicula filtrates exerted the highest inhibitions. A DNA degradation and abnormal cells were observed.